Effect of temperature on composition of produced gas in microwave pyrolysis of MSW. - Idris, Azni; Mohd Salleh, Mohamad Amran
Urban area generates significant level of waste everyday. Due to human health and environmental risk of waste disposal, waste management is a serious issue for most authorities. Disposing wastes in the landfills is costly and needs large land area. Also, there is a risk for ground water contamination, soil contamination and air pollution in addition to odor problem and hazard issues. Results of previous studies about Municipal Solid Waste (MSW) composition show that in major urban areas a significant fraction of MSW is combustible which can be used for Waste To Energy (WTE) process. In this study, a WTE process which uses pyrolysis conversion of MSW to a useful gas (Syngas) using a microwave at laboratory scale. The process is carried out in stainless steel microwave reactor with variable input power using MSW as feedstock. The gas which is produced was analyzed using gas chromatography (GC analysis). The produced gas mainly consists of Hydrogen, Nitrogen, Carbon monoxide, Carbon dioxide and methane. The results showed that waste composition, process temperature, sample residence time, microwave input power and magnetron efficiency can affect gas composition. In this paper, the effect of process temperature on gas composition is considered. Experiments conducted at 530°C, 450°C and 300°C confirmed that at higher temperatures more methane and hydrogen can be recovered using the same sample type and input power.